MICROWAVE DIELECTRICS FOR APPLICATIONS IN THE 5G FR3 RANGE - Fedorchuk, Oleksandr; V’yunov, Oleg; Plutenko, Tetiana; Belous, Anatolii (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2024)
The 5G FR3 band requires low-permittivity materials. Spinel-structured materials, like SrY2O4, are promising due to their high Q-factor and tunability. However, their practical performance limits in terms of frequency range need further investigation. Planar technologies like microstrip lines and metamaterials, using these materials as substrates, can enable efficient and high-frequency devices for 5G and beyond. This study aimed to synthesize ceramic materials with the compositions SrY2O4and SrYSmO4, possessing a spinel structure, and investigate their properties. The potential application of these materials in millimeter-wave devices and instruments was explored by modeling the spectral characteristics of antennas utilizing these materials as substrates and comparing the results with those obtained from literature-reported materials. High-purity (≥99%) SrCO3, CaCO3, Sm2O3, and Y2O3 powders were employed as starting materials. Stoichiometric quantities of the raw materials were mixed, ball-milled, dried, sieved, calcined, and re-milled. A binder was added, and the mixture was pressed into pellets. The green compacts were sintered at temperatures ranging from 1480 to 1560 °C for durations of 2–6 hours, with a heating and cooling rate of 200 °C/h. A quality factor Q×f = 89400 at a frequency of 11 GHz was achieved with a dielectric permittivity εr = 15.4 and a near zero temperature coefficient of dielectric permittivity/frequency TКε. The substitution of yttrium with samarium further decreased the dielectric permittivity to 9.4 but significantly reduced the quality factor of the material Q·f = 17800. The obtained SrY2O4 meets the requirements for dielectric materials in the centimeter wave range. It surpasses most materials in the millimeter wave range presented in the literature in terms of characteristics set. Modeling of an antenna cell based on a double split-ring resonator showed the possibility of using microstrip materials and metamaterials with substrates made of the prepared materials in the frequency range of 8.6–11 GHz and adjacent ranges, which are used in satellite communication and television systems, aviation, weather, and police radars, line-of-sight (LOS) communication systems and electronic news gathering (ENG) systems.